Virtual Tour Three Dimensions (3D) With Polygonal Modeling At Sang Nila Utama Museum - Fatdha, T Sy Eiva; Raza, Naufal Dzaky; Efendi, Yoyon (Universitas Islam Kuantan Singingi, 2022)
Sang Nila Utama Museum is an institution that functions as a place for the storage, care, safeguarding and use of objects of human culture and natural products to support efforts to protect and preserve cultural wealth. Based on the results of the surveys and interviews conducted, there are currently problems, namely 1) There is no system to present information about the collection of objects in the museum visually in 3D. 2) Due to the outbreak of Covid 19 virus, the museum management had to close the museum so far, so the public is not able to visit the museum to get information about the collection of historical relics in the Sang Nila Utama Museum. Based on the problems described above, an Android-based application for a virtual tour of exhibitions of historical objects was developed. The virtual tour is a result of the development of multimedia information technology and 3D technology that can present a 3D atmosphere. In developing this system, the Multimedia Development Life Cycle (MDLC) method was applied, which consists of several phases, namely: concept, design, material procurement, compilation, testing and distribution. This application will later run on the Android platform and use a mobile stick controller as a medium for navigation, allowing users to walk through the museum space to see a collection of historical relics in three-dimensional (3D) visual form. It is expected that this research will be one of the solutions to overcome the problems encountered in trying to improve services to the community.